Impact Counseling On Integrated Management Of Childhood Illness Influences Attitude Of Parents Brought Child Under Five Years Old Access To Health Facility - Joaquim Pinto; Carlos Boavida Tilman; Jose Dionisio Ximenes; Ana Do Rosario De Jesus Leite (PT. Banjarese Pacific Indonesia, 2024)
Handling diseases in children under five years is very important in public health because they are vulnerable to serious diseases such as pneumonia, diarrhea, malaria and malnutrition. Integrated Management of Childhood Illness (IMCI) by WHO and UNICEF is a strategy that combines prevention, treatment and health promotion, including impact counseling to provide education to parents about the importance of disease management and access to health facilities. This research uses a systematic literature review to assess the influence of impact counseling in IMCI on parents' attitudes in bringing children to health facilities. Data was collected from databases such as PubMed, Scopus, and Google Scholar using relevant keywords. Articles that met the inclusion criteria were analyzed quantitatively and qualitatively to measure the effect of counseling on parental attitudes and behavior. The results of the analysis show that impact counseling significantly increases parents' understanding and involvement in children's health care. Counseling reduces anxiety and increases parents' confidence in caring for their child. The use of information technology in counseling makes it easier to access information and support. Counseling also improves access and utilization of health facilities by providing important information about available services. In conclusion, counseling in IMCI has a significant influence on parents' attitudes and behavior in bringing children to health facilities. Counseling helps increase understanding of a child's health, reduces anxiety, and promotes better health practices at home. Ongoing counseling programs are expected to improve child health outcomes and support the overall well-being of the family.